Inseticidas químicos e microbianos no controle da lagarta-do-cartucho na fase inicial da cultura do milho - Martins, Gustavo Mamore [UNESP]; Toscano, Luciana Claudia; Tomquelski, Germison Vital [UNESP]; Maruyama, Wilson Itamar (Univ Fed Rural Semi-arido-ufersa, 2009)
The objective this work was to evaluate the effect of microbial and chemical insecticides on the fall armyworm Spodoptera frugiperda in the development initial phase of crop corn. The work was lead in the experimental area of the State University of Mato Grosso do sul, in Cassilandia (MS) city. The treatments had been: 1) control; 2) fipronil; 3) thiametoxan; 4) Beauveria bassiana (0,5 kg of p.c/ha), 5) Beauveria bassiana (1 kg of p.c/ha), 6) teflubenzuron and 7) spinosad, in the doses and recommended way of application. After the tenth second after the emergency of the plants (DAE), had been day applied the treatments in foliar spraying (PF), being evaluated to the 2, 9, 15 and 21 days after the application (DAA), the number of small caterpillars (lesser that 1,5 cm) for parcel in 20 showed plants. The applied results show that teflubenzuron and spinosad in PF to the 12 DAE had been most efficient (71 and 83% respectively). The microbial's insecticides had not differed significantly from the chemical insecticides in the percentage of plants attacked for the pest and the 15 and 21 DAA.

O objetivo do trabalho foi avaliar o efeito de inseticidas químicos e microbianos sobre a lagarta-do-cartucho Spodoptera frugiperda na fase inicial de desenvolvimento do milho. O trabalho foi conduzido na área experimental da Universidade Estadual de Mato Grosso do Sul, em Cassilândia (MS). Os tratamentos foram: 1)Testemunha; 2) fipronil; 3) thiametoxan; 4) Beauveria bassiana (0,5 Kg do p.c/ha), 5) Beauveria bassiana (1 Kg do p.c/ha), 6) teflubenzuron e 7) spinosad, nas doses e modo de aplicação recomendados. Após o décimo segundo dia após a emergência das plantas (DAE), foram aplicados os tratamentos em pulverização foliar (PF), sendo avaliado aos 2, 9, 15 e 21 dias após a aplicação (DAA), o número de lagartas pequenas (menores que 1,5 cm) por parcela em 20 plantas amostradas. Os resultados mostram que teflubenzuron e spinosad aplicados em PF aos 12 DAE foram os mais eficientes (71 e 83% respectivamente). Os inseticidas microbianos não diferiram significativamente dos inseticidas químicos na porcentagem de plantas atacadas pela praga e aos 15 e 21 DAA.
Microbial insecticides and chemical in the control of fall armyworm on crop corn
Keywords: Zea mays; lepidoptera; integrated management